Association study of candidate genes with susceptibility to heroin dependence and with methadone response in patients on methadone maintenance treatment / Diong Shiau Hui - Diong, Shiau Hui (2015)
Heroin dependence is one of various drug dependences that cause serious health and social consequences. It was reported to be the most common type of drug dependence that account for up to 45% of all drug dependence cases reported in Malaysia. Through family, adoption and twin studies, genetic factors are estimated to account for 30-70% of susceptibility to drug dependence. Heroin dependence is currently treated with methadone maintenance treatment (MMT). However, large inter-individual variability has been observed in the stabilized dose requirement, plasma concentration and response towards methadone, which can be predicted due to the involvement of genetic factors. Thus, the aim of this study is to identify the association of single nucleotide polymorphisms (SNPs) of five candidate genes with heroin dependence, MMT response and methadone dosage in Malaysian male heroin-dependent patients. Furthermore, the concentrations of methadone and its metabolite-2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) in plasma and urine of patients under MMT were monitored and the compliance of patients to the treatment were determined. There was no significant difference in genotype distributions and allele frequencies of all the five SNPs between patients and controls in the pooled subjects. However, significant difference in genotype distributions and allele frequencies was found between patients and controls in the Indian subgroup for polymorphisms of both OPRM1 rs1799971 (p = 0.037 and 0.026, respectively) and ABCB1 rs2032582 (p = 0.041 and 0.021, respectively). For OPRM1 rs1799971, the frequency of variant G allele was higher in the patients than controls with odds ratio of 2.577 (95% CI = 1.072-6.195). For ABCB1 rs2032582, the frequency of variant T allele was higher in the controls than patients with odds ratio of 0.268 (95% CI = 0.090-0.797). Besides that, GC-MS analytical method operated under selective ion monitoring mode was developed with good recovery, accuracy and precision within the range of 15-1000 ng/mL and 50-2000 v ng/mL for plasma and urine, respectively. All of the patients with urine samples collected were identified to be compliant to MMT. Methadone dosage was found to be correlated with plasma methadone concentration at trough and peak (p < 0.031). There was no significant difference in plasma methadone and EDDP concentrations as well as methadone dosage between the responders and the non-responders. Furthermore, there was no significant association of all the five SNPs with MMT response and methadone dosage. In conclusion, OPRM1 rs1799971 polymorphism was associated with increased susceptibility to heroin dependence, whereas ABCB1 rs2032582 polymorphism was associated with reduced susceptibility to heroin dependence in Indian ethnicity. The developed GC-MS analytical method can be applied as a screening tool to monitor compliance of patients with prescribed methadone. It can also be applied to identify individuals with sub-therapeutic or toxic concentrations so that adjustment of the dosage can be carried out for a more effective treatment outcome. Despite absence of association between all five SNPs with MMT response and methadone dosage, we cannot rule out the possibility of obtaining significant association if a larger sample size is used.